Information needs of a vulnerable community: The case of visually impaired first-time mothers in Malaysia - Siti Nurul Maryam; Kaur, Kiran (Malaysian Journal of Library and Information Science, 2024)
Interest in exploring women’s new experiences as they step into motherhood and their information behaviour has increased over the last decade. However, little attention has been given to vulnerable first-time mothers, specifically those with visual impairment. This study aims to provide an insight into the information needs of first-time mothers with visual impairments as they embrace motherhood. A case study design was employed to capture the information experiences of first-time mothers with visual impairment during their first year of motherhood. Three data collection techniques were employed, namely interviews, observations and audio diary, that provided rich and deep insights into the experiences of these mothers. The codes-to-theory model for qualitative inquiry resulted in identifying five main facets of information needs, namely baby care, mother care, family welfare, daily living and disability rights. Wilson’s model of information behavior is used to provide an understanding of how these mothers’ personal factors, role demands and environmental context shape their information needs as they take on the role as mothers. The findings raise implications for strategies to facilitate this vulnerable community’s information provisions, specifically in the context of visually impaired mothers.